The Rate of Contribution of some Dynamic Sense Abilities in Transmission Speed Overwhelming to Young Players - Saleh Al-Thubaini, Dr. Abdullah Hameed (International Journal of Psychosocial Rehabilitation, 2025)
Changing shares (sense of distance) is the highest proportion of the contribution of the overwhelming skillfully transmitter. The shares of the variables (the sense of force) Second skillfully contribution rate overwhelming transmitter. Changing shares (a sense of time) is the lowest rate of contribution skillfully overwhelming transmitter. Interest rates contribute to the inflexibility of the study for building a sense of the dynamics in the accuracy of the overwhelming transmitter. The adoption of the contribution rates was shown by the study of building a sense of the dynamics in the accuracy of the overwhelming transmitter. The adoption of the predict equations which reached in the evaluation of levels of Iraqi players hanging shares (sense of distance), the highest proportion of the contribution of the overwhelming skillfully transmitter. The shares of the variables (the sense of force) Second skillfully contribution rate overwhelming transmitter.